Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) : the quintessential moonlighting protein in normal cell function and in human disease /: the quintessential moonlighting protein in normal cell function and in human disease. (2017) - Sirover, Michael A
No abstract available